A Snapshot of Community Health Development Evaluation in Aotearoa New Zealand - Williamson, Yvonne Glenda (Auckland University of Technology, 2012)
In community health development (CHD) settings there is increased demand for more robust evaluation by funders of health and wellbeing initiatives who want to ensure that money is wisely invested and meets community needs. Evaluation of these initiatives is not always contracted to external professional evaluators, and increasingly more robust evaluation is expected of agencies and providers of the CHD initiatives. Therefore, within this setting there is a range of ways of doing evaluation and various perceptions about what kinds of evaluation are most appropriate. This research aimed to explore how evaluation is practised by those evaluating community based CHD in New Zealand. The perspectives of those who do evaluation, including external evaluators, programme providers, and funders were explored. Of interest were answers to the questions: ‘what kind of evaluation is being practised?’; and ‘what are the elements of successful CHD evaluation?’. This small study offers a contribution to previous research by not only considering the values and valuing experiences of professional evaluators who come from their own theoretical background, but also including the perspectives of CHD workers, providers and funders who evaluate their own programmes in CHD settings in New Zealand. Appreciative inquiry was used as a framework for conducting individual interviews with a small sample of evaluators, programme providers and a funder. Findings show differences in the three groups in that providers, because of their project management roles and accountabilities to external funders, were more focussed on project evaluation that would provide evidence of project outcomes and improved service delivery. As external agents evaluators in this study encouraged and supported providers to build their evaluative skills and capacity to carry out evaluation. The funder while concerned with accountability was still aiming to build providers capacities. It was found that although evaluation was always required, the evaluation skills in provider organisations and the funding for evaluation were often inadequate. These factors impacted on what evaluation was possible. Given that some of the concepts and values important to both CHD and evaluation are connected and overlap, and the increased demand for funders, providers and community groups to evaluate their own initiatives, it is hoped that these results will provide insights into some of the considerations for building evaluative capacity within this context, in order to advance empowerment, social justice and equity in New Zealand.
Keywords: Evaluation; Community health development; New Zealand